New Particle Formation Events Over the Southeast Atlantic Coincide With the African Biomass Burning Season - M. V. B. Oliveira; Y. Wang; M. Mehra; D. Zhang; S. J. Abel; P. Zuidema (Geophysical Research Letters)
Abstract We investigated the occurrence and evolution of new particle formation (NPF) events over the southeast Atlantic. The studied region is under the influence of the long‐range transport of aerosols and gases during the southern African biomass burning season, from June to October every year. Interestingly, NPF was observed to coincide with the African biomass burning season, although wet removal of pre‐existing aerosols is needed during these NPF events. Surface and airborne measurements show that these NPF events likely occurred in the upper region of the marine boundary layer, and the newly formed aerosols were further transported to the surface via vertical air motions. Using a box model, we predicted that a large fraction of these particles could grow to sizes related to cloud condensation nuclei. Our study shows that NPF can occur over the southeast Atlantic, and the African biomass‐burning plume likely contributed to the NPF occurrence.